Does the benefit of salvage amputation always outweigh disability in drug-failure mycetoma?: A tale of two cases - Prasanta K Maiti; Bipasa Chakraborty; Sudipta Ghosh; Abhishek De (Wolters Kluwer Medknow Publications, 2015)
It is popularly believed that eumycetoma cases should be dealt with using surgical amputation for a better chance of cure especially when chemotherapy has failed. However, amputation leads to disability on one hand and on the other it may also fail to be curative. We present two cases with contrasting treatment options and outcome. In the eumycetoma case reported here, a 40-year-old male presented with right foot swelling for 16 years, from which Scedosporium apiospermum was isolated. He responded poorly to antifungal therapy and refused below-knee amputation 12 years ago. With counseling and wound care his condition improved, and Foot and Ankle Ability Measure (FAAM) score remained almost stable at 90% for 16 years, which is much better than the average functional outcome after amputation. Another 46-year-old female underwent below-knee amputation after receiving incomplete courses of antibiotics and antifungals for mycetoma of unknown etiology. She presented to us after recurrence of mycetoma on an amputated stump and was successfully treated by proper courses of antibiotics after detecting the causal agent, Actinomadura madurae. Her post-amputation disability and depression could have been avoided if the hasty decision of amputation had not been taken. In our opinion, living with drug-non-responsive mycetoma, supported by symptomatic management, may be a better option than amputation and its associated morbidities. So before taking the path of salvage amputation, we must consider many aspects, including patient's livelihood, psychological aspects and chances of recurrence even after the procedure.